Prelacteal feeding is not associated with infant size at 3 months in rural Bangladesh: a prospective cohort study - Hannah Tong; Andrew Thorne-Lyman; Amanda C. Palmer; Saijuddin Shaikh; Hasmot Ali; Ya Gao; Monica M. Pasqualino; Lee Wu; Kelsey Alland; Kerry Schulze; Keith P. West, Jr; Md Iqbal Hossain; et al. (BMC, 2024)
Abstract Background Early and exclusive breastfeeding may reduce neonatal and post-neonatal mortality in low-resource settings. However, prelacteal feeding (PLF), the practice of giving food or liquid before breastfeeding is established, is still a barrier to optimal breastfeeding practices in many South Asian countries. We used a prospective cohort study to assess the association between feeding non-breastmilk food or liquid in the first three days of life and infant size at 3-5 months of age. Methods The analysis used data from 3,332 mother-infant pairs enrolled in a randomized controlled trial in northwestern rural Bangladesh conducted from 2018 to 2019. Trained interviewers visited women in their households during pregnancy to collect sociodemographic data. Project staff were notified of a birth by telephone and interviewers visited the home within approximately three days and three months post-partum. At each visit, interviewers collected data on breastfeeding practices and anthropometric measures. Infant length and weight measurements were used to produce length-for-age (LAZ), weight-for-age (WAZ), and weight-for-length (WLZ) Z-scores. We used multiple linear regression to assess the association between anthropometric indices and PLF practices, controlling for household wealth, maternal age, weight, education, occupation, and infant age, sex, and neonatal sizes. Results The prevalence of PLF was 23%. Compared to infants who did not receive PLF, infants who received PLF may have a higher LAZ (Mean difference (MD) = 0.02 [95% CI: -0.04, 0.08]) score, a lower WLZ (MD=-0.06 [95% CI: -0.15, 0.03]) score, and a lower WAZ (MD=-0.02 [95% CI: -0.08, 0.05]) score at 3-5 months of age, but none of the differences were statistically significant. In the adjusted model, female sex, larger size during the neonatal period, higher maternal education, and wealthier households were associated with larger infant size. Conclusion PLF was a common practice in this setting. Although no association between PLF and infant growth was identified, we cannot ignore the potential harm posed by PLF. Future studies could assess infant size at an earlier time point, such as 1-month postpartum, or use longitudinal data to assess more subtle differences in growth trajectories with PLF. Trial registration ClinicalTrials.gov: NCT03683667 and NCT02909179.